Dry Sliding Wear Behavior of AA 7075 Reinforced Short Coated Carbon Metal Matrix Composites - Suhas, P.; Vaishak, N.L.; Quadros, J. D. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
The dry sliding wear characteristics of aluminum alloy 7075 reinforced with short coated carbon fiber metal matrix composites were analyzed using pin on disc apparatus. The carbon fibers were used at different wt. % of 1, 2 and 3% respectively. Stir casting method was used to prepare the cast composites. For proper wettability, the carbon fibers were coated with nickel using the principle of autocatalytic reduction. It was observed that the wear rate decreased by a maximum of 16.23% for normal load of 10N and 38.46% for sliding distance of 500m. Structure-property correlation also formed a basis for a thorough and clear understanding of the prepared composite subjected to wear parameters. It is observed that unreinforced AA 7075 composite showed heavy delamination and fracture of the transfer layer due to the abrasive action of the hardened transfer particles resulting in flake like debris.